Laparoscopic management of tumor in supernumerary ovary - Ved Prakash; Anita Kant; Abha Parashar; Uma Rani (Wolters Kluwer Medknow Publications, 2016)
Laparoscopic management of most of the adnexal masses has become feasible in the present era of advancing endoscopic techniques. A postmenopausal lady presented with lump in the abdomen, appeared to be a solid ovarian mass on ultrasound, and magnetic resonance imaging. On laparoscopy, both the ovaries were normal and the mass was not connected to uterus or adnexa. The mass was removed and histopathology confirmed it to be ovarian tissue thus confirming it to be a tumor in a supernumerary ovary. Examples of supernumerary ovary are among the rarest of gynecological abnormalities.